Estudo bibliométrico em finanças: análise da produção científica brasileira de 2009 a 2018 - Holanda, Kaline Pontes (Universidade Federal Rural do Semi-Árido, 2019)
Scientific production in the area of finance in Brazil is vast, but it faces some problems such as academic productivism, foreignism and parochialism. Many works have been done in the area until then, however few are those who propose to make a general and current overview of the area. Based on this evidence, this paper aims to analyze the scientific production of EnANPAD and the Revista com Qualis Capes ≥ B1 in the area of finance from 2009 to 2018, as well as to identify which are the most approached subjects in the subareas of traditional finance and behavioral finance, check which are the most prolific authors and find out which are the most published articles in the area. For that, a bibliometric study was carried out with 899 articles through two softwares: Mendeley and VOSviewer. It was verified that the number of articles published in the area varies according to the database and the subarea analyzed, that the distribution of academic production is divided into two groups: one with a large number of authors who published only one article and the other another with a small number of authors producing a large number of articles, and that there is a core of periodicals belonging to the accounting area that most published articles on finance studied on tha period. It was also observed that in the sub-area of behavioral finance, the subjects on "financial literacy" were the most recurrent, while the themes on the capital market and public companies were the most discussed in the traditional finance articles, represented by the word "Brazilian publicly traded companies". It is concluded that the publications are focused on issues about large corporations, observing the need for papers that deal with everyday issues of small and mediumsized companies that were little discussed in the articles analyzed.
Monografia
Keywords: Finanças; Finanças tradicionais; Finanças comportamentais; Revistas Qualis-Capes; Bibliometria; EnANPAD; Finance; Traditional Finance; Behavioral Finance; Qualis-Capes journals; Bibliometry; EnANPAD; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO